Nabais Sa-de Vries Syndrome and Thalassemia: An Undiscovered Concurrence of SPOP and HBB Genetic Mutation - Muhammad Matloob Alam; Abdulrhman Alathaibi; Badriah Gharamah Alasmari; Mohammad Aljabri; Muhammad Kashif; Riffat Matloob; Mustafa Mohamed Selim (The Korean Society of Pediatric Hematology-Oncology, 2024)
Nabais Sa-de Vries syndrome (NSDVS) is a neurodevelopmental disorder first described in 2020. The syndrome is caused by de novo missense mutations in speckle-type pox virus and zinc finger protein (SPOP) on chromosome 17q21. In this report, we present a four-year-old girl who had microcephaly, a long face, a wide and thick arched eyebrow, widely spaced eyes, a prominent and wide nasal bridge, a wide and bulbous nasal tip, micrognathia and pointed chin. She also had microcytic hypochromic anemia. Her clinical features are suspected of NSDVS1 and thalassemia along with refractory iron deficiency anemia. Genetic evaluation confirmed the presence of both SPOP and hemoglobin gene mutations. The concurrence of both genetic mutations and above hematological manifestations has not been reported previously thus further studies are needed to better understand the associated mechanisms and disease course involved.